The Impact of MERDEKA Path-Based Project Based Learning Model on Self-Efficacy in Primary School Mathematics Learning - Anisa Khayati Nur Kafah; Fery Muhamad Firdaus; Irman Artobatama (Jurnal Ilmiah Sekolah Dasar, 2024)
Merdeka Belajar is currently a primary goal in the learning process, driven by students' needs. Not only character, but students must also possess soft skills to face the challenges of the 21st century. Self-efficacy is important for students to have confidence and determination in performing tasks, making the learning process effective and positively impacting their learning outcomes. This study aims to analyze the impact of the MERDEKA path-based Project-based Learning (PjBL) model on self-efficacy in mathematics. This study employs a quasi-experimental design with a one-group pretest-posttest design, involving 22 students from the fourth grade as a saturated sample. The research instruments include a self-efficacy questionnaire and a test. Data analysis was conducted using descriptive analysis and Paired Sample t-Test. Prior to hypothesis testing, prerequisite tests including normality and homogeneity tests were performed. The results indicate that the implementation of the MERDEKA path-based PjBL model can improve students' self-efficacy compared to before the treatment. This is evident from the increase in the average score of students, from 62.09 before the treatment to 79.31 after the implementation of the MERDEKA path-based PjBL model. The t-test results show tcount ≥ ttable (17.422 > 2.05954), indicating that H0 is rejected and H1 is accepted. Therefore, it can be concluded that the MERDEKA path-based PjBL model has a positive impact on students' self-efficacy in fourth-grade primary school mathematics.